Prevalence of Percutaneous Injuries and Associated Factors Among a Sample of Midwives in Hunan Province, China. (September 2020) - Cao, Wenjing; Cao, Nanlin; Gu, Mei; Li, Pan; Li, Min; Luo, Chan; Liu, Henghui; Jiang, Fuyun; Li, Chunyan; Cao, Shunwang
Background: Percutaneous injuries and blood-borne-related infections pose occupational hazards to healthcare professionals. However, the prevalence and associated factors for these hazards among midwives in Hunan Province, China are poorly documented. Methods : A cross-sectional study was conducted among a sample of 1, 282 eligible midwives in the cities of Yongzhou, Chenzhou, Hengyang, and Changsha in Hunan Province, China, from January 2017 to July 2017. The association of selected independent variables with percutaneous injuries was investigated using binary logistic regression. Results : 992 participants responded (77.3%), and within the previous 12 months, 15.7% experienced percutaneous injuries. In multivariate analysis, hospital size, age, length of employment as a midwife, weekly working hours, and three aspects of Hospital Safety Climate Scale were associated with percutaneous injuries. The risk of percutaneous injuries among the midwives working in hospitals with ≤399 beds was higher than that among those working in hospitals with ≥400 beds by nearly 3 times. Furthermore, the percutaneous injury prevalence of midwives decreased as age increased. Moreover, the probability of percutaneous injuries among the midwives with weekly working hours of >40 was 4.35 times higher compared with that among midwives with weekly working hours of ≤40. Conclusion/Application to practice : The prevalence of percutaneous injuries among midwives in the study hospitals was substantial. Our results further proved that risk mitigation strategies tailored to midwives are needed to reduce this risk. These strategies include ensuring a positive organizational climate, providing highly safe devices, and reducing the workload.